Improving The Performance of Asphalt Concrete Mixtures With Polymer Asphalt in Submerged Floods - Yanuar Setiawan; Erlina Yanuarini; Nunung Martina; Muhammad Fathur Rouf Hasan; Rinawati Rinawati (POLITEKNIK NEGERI JAKARTA, 2021)
The road conditions which is always submerged can reduce the performance of the asphalt pavement. This research was conducted to obtain the characteristics of polymer asphalt concrete against flooding. Marshall testing was carried out on conventional and polymer asphalt concrete with optimum asphalt content treated with water immersion in variations of 0 days, 0.5 days, 1 day, 2 days, and 4 days. The results show polymer asphalt can improve the durability of asphalt concrete which is submerged in floodwater. This is indicated by the difference in the stability value of 113% in the variation of immersion for 4 days.